The Evolution Of Grounds For Divorce in Islamic Family Law: an Analysis of The Theory of Legal Change and The Practice of Religious Courts in Indonesia - Roli Wilpa; Isep Rijal Muharom; Agus Gandara; Beni Ahmad Saebani (Dinasti Research, 2026)
This study aims to analyze the transformation of grounds for divorce in Islamic family law in Indonesia through an integrative approach combining legal change theory, maqāṣid al-syarī‘ah, and the practices of religious courts. The main issues addressed include the normative construction of grounds for divorce in Islamic law, the development of grounds for divorce in Indonesian positive law, and the relevance of legal change theory in explaining such dynamics. This research employs a normative juridical method with conceptual, statutory, and socio-legal approaches. The findings reveal that, normatively, grounds for divorce in Islamic law are derived from the Qur’an, Hadith, and classical fiqh, which position divorce as a last resort (ultimum remedium) with limited justifications, such as failure to provide maintenance, physical defects, and severe marital discord (shiqāq). However, in Indonesian positive law, particularly through the Marriage Law and the Compilation of Islamic Law, there has been an expansion and codification of grounds for divorce in a more flexible manner. In judicial practice, religious court judges actively engage in contextual interpretation, whereby the category of “continuous disputes and quarrels” evolves into an umbrella clause encompassing psychological conflict, emotional abuse, and even digital-related issues. This transformation can be explained through legal change theory, which views law as a dynamic system responsive to social change. The maqāṣid al-syarī‘ah approach provides normative legitimacy for such flexibility by emphasizing the protection of welfare (maṣlaḥah) and the prevention of harm (mafsadah). Accordingly, Islamic family law in Indonesia demonstrates characteristics of a progressive, contextual, and substantively just legal system, with judges acting as agents of legal transformation.